2020
DOI: 10.3390/molecules25204669
|View full text |Cite
|
Sign up to set email alerts
|

Elicitor-Induced Production of Biomass and Pharmaceutical Phenolic Compounds in Cell Suspension Culture of Date Palm (Phoenix dactylifera L.)

Abstract: Plants that synthesize bioactive compounds that have high antioxidant value and elicitation offer a reliable in vitro technique to produce important nutraceutical compounds. The objective of this study is to promote the biosynthesis of these phenolic compounds on a large scale using elicitors in date palm cell suspension culture. Elicitors such as pectin, yeast extract (YE), salicylic acid (SA), cadmium chloride (CdCl2), and silver nitrate (AgNO3) at 50, 100, and 200 mg/L concentrations are used. The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 33 publications
5
9
0
Order By: Relevance
“…Natural polysaccharide pectin present in plant cell walls improved the biomass accumulation and secondary metabolite stevioside content in in vitro micro-propagated Stevia rebaudiana cultures (Bayraktar et al 2016 ). Our results corroborate the study of Al-Khayri and Naik ( 2020 ) on Phoenix dactylifera where PE (50 mg/L) enhanced the flavonoid contents in cell cultures. Similarly, Cai et al ( 2012 ) found enhanced production of phenolic acids and anthocyanin upon exposure to pectin in Vitis vinifera cell cultures (Cai et al 2012 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Natural polysaccharide pectin present in plant cell walls improved the biomass accumulation and secondary metabolite stevioside content in in vitro micro-propagated Stevia rebaudiana cultures (Bayraktar et al 2016 ). Our results corroborate the study of Al-Khayri and Naik ( 2020 ) on Phoenix dactylifera where PE (50 mg/L) enhanced the flavonoid contents in cell cultures. Similarly, Cai et al ( 2012 ) found enhanced production of phenolic acids and anthocyanin upon exposure to pectin in Vitis vinifera cell cultures (Cai et al 2012 ).…”
Section: Discussionsupporting
confidence: 91%
“…Elicitation with YE has successfully increased caffeic acid in Echinacea puprea callus cultures (Rady et al 2018 ), asiaticoside in Centella asiatica and plumbagin in Drosera burmanii whole plant cultures (Kim et al 2004 ; Putalun et al 2010 ) and mitragynine in shoot cultures of Mitragyna speciose (Wungsintaweekul et al 2012 ). Per our results, YE (50 and 100 mg/L) downregulated the apignenin production, while in the contrary, decreased the caffeic acid and apignenin accumulation in the presence of PE and YE in Phoenix dactylifera cell suspension cultures (Al-Khayri and Naik 2020 ). Phytochemicals quantified in A. integrifolia micro-shoot cultures have pharmaceutical importance, especially as antioxidant agents, disrupting cancer cellular machinery, suppression of oncogenes and apoptosis of cell (Mohammad Nabavi et al 2015 ; White et al 1989 ).…”
Section: Discussionsupporting
confidence: 70%
“…After elicitation with YeE, the total amount of polyphenols and flavonoids decreased in our study (Table 2 and Supplementary Table S2 ). Stimulation of the production of total flavonoids and total polyphenols has also been demonstrated for cell suspension cultures of Phoenix dactylifera (Al-Khayri and Naik 2020 ), Orostachys cartilaginous (Wen et al 2019 ), and shoot cultures of Artemisia aucheri (Abbaspour and Ehsanpour, 2016 ) after treatment with SA as elicitor. In extracts from B. oleracea cell suspension cultures, the total amount of polyphenols also increased after elicitation with MeJA (Sánchez-Pujante et al 2020 ).…”
Section: Discussionmentioning
confidence: 86%
“…importance to choose an elicitor at the optimum level required for callus induction. 22 Among the elicitors the highest callus fresh weight (0.60 and 0.61 g) was obtained in 5/10 and 10/10 min/cm UV-C treatment.…”
Section: Influence Of Elicitors On Callus Formation and Morphological...mentioning
confidence: 87%